Features of Integration Conjuncture and its Prognosis - Sūdžius, Vytautas; Mackevičius, Vytautas (Ekonomika, 2003)
The article is devoted to features and, researching of conjuncture.Making conjuncture review is the most efficient way to describe economical situation in Lithuania. The article defines main features of market conjuncture, describes economical and other important factors, which have intense influence on conjuncture and offers mode] of conjuncture review and prognosis.Conjuncture reflects all variable relations between supply and demand of market economy. It has peculiar features and specific formation mechanism, taking into account different factors, conditions and economical circumstances.Conjunctures the tendency of its changes in current economical situation is the main economical indicator. According to the indicator we can forecast whether tendency in demand and supply grow or fall. So, indicator value will influence the strategic decisions concerning the future of a company.Conjuncture is the main tool to describe current economical situation and helps to take reasonable decisions when trade is developing rapidly. Enterprise conjuncture may be defined narrower precisely - as conjuncture of regional market area, special goods and services. The factors can be divided into such groups: cyclical and encyclical, which have influence on the national economic level and regional economic level, export/import and market infrastructure.